2002
DOI: 10.1080/10587250210577
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Morphological Changes and Optical Writing in a Liquid Crystalline Polymer on the Micron and Sub-Micron Scale

Abstract: In this paper we describe our recent work on optical effects due to photoinduced molecular reorientation in a side chain liquid crystalline polymer, namely azopolymethacrylate (PMA4). We have studied several kinds of optical effects on space scales ranging from the nanoscopic to macroscopic. In particular, we have built a computer controlled microscope-based apparatus to study photoinduced effects down to the micron scale in thin and ultrathin (Langmuir Blodgett) films of our material. Furthermore we measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Interestingly, Figure b,c shows that the film morphology is unchanged when the surface is irradiated with a LED at 365 nm. The obtained results are in good agreement with the data reported in literature related to the formation of nanostructures on the surface of AZO/P­(M)­A polymers, as well as with the formation of an intermediate phase of reorganization. , In particular, the morphological rearrangement only occurs if the LC polymer is not in its glass phase at the operating temperature condition. With regard to our systems, at RT only PA-AZO1 is in its nematic LC phase ( T g = 19 °C), explaining why it undergoes a dramatic morphological reorganization when irradiated with UV–vis light. , Moreover, Angiolini et al have reported that the PA-AZO1 the isomerization from trans to cis generates a contraction of the material.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Interestingly, Figure b,c shows that the film morphology is unchanged when the surface is irradiated with a LED at 365 nm. The obtained results are in good agreement with the data reported in literature related to the formation of nanostructures on the surface of AZO/P­(M)­A polymers, as well as with the formation of an intermediate phase of reorganization. , In particular, the morphological rearrangement only occurs if the LC polymer is not in its glass phase at the operating temperature condition. With regard to our systems, at RT only PA-AZO1 is in its nematic LC phase ( T g = 19 °C), explaining why it undergoes a dramatic morphological reorganization when irradiated with UV–vis light. , Moreover, Angiolini et al have reported that the PA-AZO1 the isomerization from trans to cis generates a contraction of the material.…”
Section: Resultssupporting
confidence: 90%
“…The obtained results are in good agreement with the data reported in literature related to the formation of nanostructures on the surface of AZO/P(M)A polymers, 12 as well as with the formation of an intermediate phase of reorganization. 38,39 In particular, the morphological rearrangement only occurs if the LC polymer is not in its glass phase at the operating temperature condition. With regard to our systems, at RT only PA-AZO1 is in its nematic LC phase (T g = 19 °C), explaining why it undergoes a dramatic morphological reorganization when irradiated with UV−vis light.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…All of these issues can be studied in a specific class of materials, namely side-chain liquid crystalline polymers with an azobenzene moiety attached to the main chain via a flexible molecular spacer [3][4][5]. In polyacrylates and poly-methacrylates the pumping of the photo-isomerization transition yields several potentially useful optical effects with very high sensitivity [6][7][8]. The vibrational and diffusive dynamics can be altered by the optical pump [9,10] and the phenomenology of the glass transition has been extensively studied by calorimetric, dynamical analysis and ESR relaxation measurements [11].…”
Section: Introductionmentioning
confidence: 99%
“…In polyacrylates and poly-methacrylates the pumping of the photo-isomerization transition yields several potentially useful optical effects with very high sensitivity [6][7][8]. The vibrational and diffusive dynamics can be altered by the optical pump [9,10] and the phenomenology of the glass transition has been extensively studied by calorimetric, dynamical analysis and ESR relaxation measurements [11].…”
Section: Introductionmentioning
confidence: 99%
“…This (noting that the corresponding ω-values are very similar) indicates that the trans isomer is far more rigid than the cis form. It is commonly accepted in the literature [6,19,20] that isomerization causes fluidification of azo polymers, although no quantitative direct data have been published so far. Here we have a clear observation of this fact.…”
Section: Surface Quasielastic Light Scatteringmentioning
confidence: 99%